Traditional concepts of typology of the state - Baizhanova, G.T. (Publ.KarSU, 2017)
The article expresses the view about the necessity of the refusal from certain one-sidedness of the theoretical and methodological principles dominating for decades. State typology is classified leaning on domestic and foreign literature, state types are considered from a perspective of classical understanding and modern approaches taking into account distinctive and defining criteria. Different concepts of typology perform different functions in the process of state learning. The criteria and results of the state typology give the grounds to unite the widespread formational, civilizational and integrative concept into traditional (classical) group. The traditional concept explores the most common factors and criteria for the state development, focuses on the nature of economic and political relations, cultural, spiritual and religious factors of the state development.
Мeмлeкeт типoлoгияcының дəcтүpлi тұжырымдамалары
Тpaдициoнныe кoнцeпции типoлoгии гocудapcтвa
Keywords: typology; type; state typology; state type; Asian mode of production; stratum concept; civilization concept; integrative concept; ideological concept; concept of the state and power organization; concept of legal status of the citizen; information concept; concept of the right development; concept of social production; social state